Mental Health Status of Canadian Funeral Service Workers at the Beginning of the COVID-19 Pandemic. Issue 6 (June 2021) - Durand-Moreau, Quentin; Galarneau, Jean-Michel
Abstract : Objective: To describe the mental health situation and job stress levels of Funeral Service Workers (FSW) during the first months of the pandemic. Methods: We conducted a cross-sectional study in Canada between May and July 2020. Funeral service professional organizations were asked to spread a questionnaire to their members including job description, assessment of anxiety (GAD-7), depression (PHQ-8), and job stress (effort-reward imbalance questionnaire). Results: Fifty-eight FSW completed a questionnaire, 32% reported anxiety symptoms (GAD-7 > 10), 29% reported depressive symptoms (PHQ-8 > 10), 31% reported job stress. Women were more likely to report overcommitment (66.7% vs. 31.8%, P = 0.015). Conclusions: Levels of anxiety and depression identified in Canadian FSW were higher than those identified in other occupational groups during the first few months of the pandemic. Abstract : Supplemental Digital Content is available in the text